Hubungan Tingkat Pengetahuan Dan Sikap Masyarakat Tentang Dagusibu Obat Di Desa Lebakwangi Kecamatan Arjasari Kabupaten Bandung - Roni, Asep; Sri Mas Hartini, Ni Nyoman; Dista Asmarani, R. Mayang (JURNAL FARMASI GALENIKA, 2024)
DAGUSIBU is an effort to improve health for the community which is carried out through health service activities by pharmaceutical staff. DAGUSIBU (Get, Use, Save, Throw Away) is a Drug Awareness Family Movement Program initiated by the Indonesian Pharmacists Association to achieve public understanding and awareness of the correct use of drugs. Based on the results of Riskesdas Basic Health research in 2013, it shows that 35.2% of households store medicines for self-medication. Referring to the 35.2% of households that store medicines, 35.7% of them store hard medicines, and 27.8% of them store antibiotics and 86.1% of these antibiotics were obtained without a prescription. The aim of this research is to find out to what extent the general public in Lebakwangi Village, located in Arjasari District, Bandung Regency, knows about Dagusibu medicine. The method used in this research is descriptive quantitative using a One Group Pretest and Posttest design with an accidental sampling approach. The results of the research showed that having a level of knowledge in the good category regarding DAGUSIBU Medicine had increased by 27%, and having a level of attitude towards DAGUSIBU Medicine in the good category had increased by 16%. The level of public knowledge is related to attitudes. Based on the results of the Spearman correlation test, it shows a p value of 0.048.